Dust Exposure in the Stone Carving Industry and Its Impact on Respiratory Health: An Environmental Risk Assessment - Sutaryono Sutaryono; Rezyana Budi Syahputri; Heru Subaris Kasjono; Tuti Susilowati; Teguh Setyadi; Purwanti Purwanti; Sukamsi Sukamsi; Dhanik Ernawati; Mohamad Samsudin; Taufiq Hidayat (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Stone carving in Magelang Regency holds significant potential to enhance community welfare through industrial and tourism development, but it also presents health risks due to PM10 dust exposure exceeding safe limits. This study aims to identify respiratory health risks of stone craftsmen due to dust exposure with the incident of respiratory diseases, using a quantitative approach with observations and primary data collection from 60 respondents. Dust levels were measured using LVDS and HVDS, while the prevalence of Acute Respiratory Infections (ARI) was determined through health examinations. Environmental Health Risk Analysis (ARKL) with the Risk Quotient (RQ) was applied to evaluate long-term exposure. Results showed dust concentrations of 12.941 mg/m³ in Sedayu and 17.647 mg/m³ in Banyudono, both above the threshold, with respiratory disorders more prevalent in Sedayu (53.3%) than in Banyudono (33.3%). RQ values above 1 in both villages indicate significant health risks, highlighting the need for improved PPE use, ventilation, routine air quality checks, and health monitoring to prevent respiratory issues.